2015
DOI: 10.1371/journal.pone.0131017
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Dopamine Transporter Availability and Neurocognitive Deficits in Male Patients with Alcohol Dependence

Abstract: Dopamine plays an important role in the development of alcohol dependence, cognitive dysfunction, and is regulated via dopamine transporter activity. Although dopamine transporter activity is critically involved in alcohol dependence, studies observing this relationship are limited. Thus the current study examined whether dopamine transporter availability is associated with developing of alcohol dependence and cognitive dysfunction. Brain imaging with 99mTc-TRODAT-1 as a ligand was used to measure dopamine tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…3, Table 4). These results are consistent with our previous study [10] and other studies in human, [45,46] which suggest that striatal dopaminergic function may play an important role in performance on cognitive tests.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…3, Table 4). These results are consistent with our previous study [10] and other studies in human, [45,46] which suggest that striatal dopaminergic function may play an important role in performance on cognitive tests.…”
Section: Discussionsupporting
confidence: 94%
“…Of the different subgroups we examined, this study found that the pure AD group exhibited the lowest DAT availability compared to that in the AD/MD and control groups. Our results are similar to prior neuroimaging studies in patients with AD, [8,10,11] but differ from those of others. [26,27] …”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations